Qualitas: uma modelo de processo de desenvolvimento de software orientado a modelos - Almeida, Carla Cássia de Jesus (2014)
The Model Driven Development (MDD) is a paradigm of development of software products, whose objective is to put the models as the main artifact of the development process, instead of putting the source code. In recent years, researches in Software Engineering area have created and adjusted definitions, methods and structures for the achievement of this paradigm. However, the models of the software development process, as well as testing activities involved in these models are not adequate and do not allow the effective use of this paradigm. In order that the Software Engineering area has as it main goal, the development of software products with quality, it is also necessary that these models of the development process involves increasingly approaches to software testing, with the intent to commit them from the early stages, aiming to identify and correct the errors as soon as possible, adding quality to the software. An approach that uses models in software testing is the Model Driven Testing (MDT), which one makes use of the MDD practices, through the automatic generation of test artifacts according to the rules of predefined transformation from development models. Thus, this work presents the Qualitas, a model for the development of model-driven software, which allows the use of both models in the effective integration of MDD and MDT. The model seeks to promote a greater control of the stages and activities of the software development process, but also to add quality to software products developed. A review and an experimental study of Qualitas was performed through the implementation of activities related to the Federal University of Sergipe (UFS) Neonatal Screening System of the University Hospital (HU) functionality, highlighting the advantages and limitations of the model presented.